Do the presence, size, and shape of plantar calcaneal spurs have any significance in terms of pain and treatment outcomes in patients with plantar fasciitis - OKÇU, MEHMET (My University, 2023)
Background/aim: The purpose of this study was to determine the effect of the presence, size, or type of calcaneal spurs on pain or the outcomes of extracorporeal shock wave therapy (ESWT) therapy in patients with plantar fasciitis.Materials and methods: Seventy-four patients with unilateral plantar fasciitis who had no pain in the contralateral foot, either currently or in the past, were included in the study. The length, base width, type, and presence of plantar calcaneal spurs in both heels of the patients were determined using radiography. A total of five sessions of ESWT (3 bar, 2000 shocks/session, 12 Hz frequency) with an interval of 3 days were performed on the painful sides of the patients. Symptom duration and numerical rating scale (NRS) scores were recorded pretreatment and 1 week and 12 weeks after treatment.Results: Spurs were detected in 85.1% of painful feet and 71.6% of painless feet, this difference was statistically significant (p = 0.046). There was no significant correlation between the type of the spurs and whether the foot was painful. Patients with spur sizes of >5 mm or with horizontal and hooked spurs had a higher NRS decrease than patients with spur sizes of <= 5 mm or with a vertical spur. Symptom duration, spur length, and base width were found to be correlated with pretreatment NRS scores.Conclusion: The presence and size of calcaneal spurs are associated with pain. However, it should be kept in mind that a high rate of spurs can also be found in painless feet, so spur is not the only factor that causes pain. Patients with a spur size of <= 5 mm or a vertical spur have less pain relief with ESWT.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Calcaneal spur; plantar fasciitis; size; type; extracorporeal shock wave therapy; pain; SHOCK-WAVE THERAPY; DIAGNOSIS; CLASSIFICATION; Calcaneal spur; plantar fasciitis; size; type; extracorporeal shock wave therapy; pain